Processo de Produção de Ilustração Biológica para Conservação de Megaxenarthra: Myrmecophaga tridactyla (Linneaus, 1758) e Priodontes maximus (Kerr, 1792) - Busana, Pedro Rodrigues (Universidade Federal de São Carlos, 2018)
Biological illustration is a tool of graphic representation of phenomena and components of the Biological Sciencesthat is considered to be part of scientific illustration. In addition to its already well-known use in taxonomy, paleontology and medical sciensces, it can be applied in the elaboration of materials for scientific dissemination and environmental education, being an important ally for conservation biology. This work aimed to answer the question "how can illustration help endangered species?", using as a model Myrmecophaga tridactyla (Linnaeus, 1758) and Priodontes maximus (Kerr, 1792), both considered vulnerable species according to the IUCN. Asurvey gathering reference material for each species (photographs, illustrations and videos) was initially carried out. Animals were also observed at zoos, breeding grounds and at their natural environment). Andsemi-structured interviews with specialists in each species(biologists, veterinarians, zootechnicians and keepers) was also used to collect data. The valuation of the opinions of different professionals directed the content to be illustrated critically, focusing on issues related to habitat loss, unique morphology representation and description of the behavioral aspects related to both parental care and self-maintenance. The drawings were made using realistic techniqueswith bothpencil on paper and digital painting, aiming at the general public as the target audience. In the future these drawings will be made available to the institutions participating in this study and used on books, signs and other didactic materials to be usedin environmental education and conservation of the species portrayed. The use of interviews and direct observations to guide illustration based science communication proved to be decisive in creatinga contemplative link of the researcher with its organisms of study, avoiding distortions of the speech or of the nature of the animals.We hope with this to shorten the gap between the knowledge produced by the scientific community and the society in general and to enhance the participation of scientific illustrations in conservation biology.
Production process of Biological Illustration for Megaxenarthra conservation: Myrmecophaga tridactyla (Linneaus, 1758) and Priodontes maximus (Kerr, 1792)
Keywords: Ilustração científica; Conservação in situ/ex situ; Tamanduá-bandeira; Tatu-canastra; Scientific illustration; In situ/ex situ conservation; Giant anteater; Giant armadillo; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS